Technical study of the effect of laser engraving using uArm swift pro robot - Mondal, Soumen; Dutta, Ajoy Kumar (Institute of Advanced Engineering and Science, 2021)
Laser engraving is the most non - traditional and efficient working method in the machining of materials of different geometry as compared to conventional methods. The main objective of this study is to determine the impact of uArm swift pro robot operated laser engraving process on a wooden pitch board piece. However, the robot was connected with uArm Studio 1.1.22 software to perform laser engraving operation. For this purpose the effect of process parameters like spot diameter and depth of penetration were investigated with different working length of the robot end effector, measured from wooden pitch board base. Experimental observation method was used to investigate the formation of deep and light engraving pattern on the pitch board surface by measuring penetration depth and spot diameter in suitable condition. The result obtained from the experiment and statistical parameters showed a new dimension to find a suitable working length of the robot assisted laser nozzle where the laser penetration effect was clearly perceptible for the wooden material.